Hypoglycemia in Patients With Pure Benzodiazepine Poisoning: Hypoglycemia in patients with pure benzodiazepine poisoning - Goudarzi, Fazel; Mousavi-Roknabadi, Razieh Sadat; Abdollahpour, Maryam; Sadegh, Robab (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Various studies investigated the effects of benzodiazepines on insulin and blood glucose levels and provided contradictory results. The present study aimed to evaluate the clinical effects of benzodiazepine poisoning on hypoglycemia. Methods: This retrospective cross-sectional study (from 22/June/2018 to 22/December/2018) was conducted on all medical records of adult patients with benzodiazepine poisoning who were referred to Ali-Asghar Hospital. The required data were collected using a data-gathering form and then analyzed. Results: In total, 61 patients were enrolled in this study. Furthermore, 19 (31.2%) patients developed hypoglycemia. Besides, 50 (82%) patients used benzodiazepine for a suicide attempt, i.e. higher in patients with hypoglycemia (P<0.0001). Multivariate logistic regression test data indicated that benzodiazepine consumption for suicide attempt (OR=47.978, P=0.001, 95%CI, 5.313-433.277), and the respiratory rate at the time of suicide (OR=0.549, P=0.023, 95%CI, 0.328-0.920) were predictive factors for hypoglycemia in patients with benzodiazepine poisoning. Conclusion: Our study data suggested that 31% of patients who were poisoned with benzodiazepines developed hypoglycemia. The suicidal use of drugs and respiratory rates were predictive factors for hypoglycemia in these patients.